Kinerja Reproduksi Induk Sapi Sebelum dan Sesudah Pendampingan pada Kelompok Tani Lembu Agung, Distrik Kurik, Kabupaten Merauke - Batseba M.W. Tiro (Jurnal Ilmiah Inovasi, 2017)
Extensive land and diversity of local feed sources allows Papua to have great potential in the development of beef cattle. However, with the traditional livestock breeding system, where livestock is only released and feed still depends on the availability of nature it will certainly affect the productivity of livestock. In addition, farmers have not mastered the feed technology appropriately so that the source of feed has not been utilized optimally to support the growth of livestock. The long dry season in Merauke Regency has an impact on the limited of forage feed in terms of quality and quantity that directly affect the productivity of livestock. On the other hand, the extent of rice cultivation area in Merauke Regency by itself is enough rice cultivation available potentially as beef cattle feed, but the potential has not been optimally utilized. Strategic measures need to be taken such as improving maintenance systems through technological assistance at the farm level. This study aims to present data and information on the reproductive performance of beef cattle before and after assistance in the farming of beef cattle in the Lembu Agung Farmer Group, Kurik District, Merauke Regency. The results of technological assistance at the farm level through improved feeding on parent beef cattle can improve the performance of the parent rerpoduksi that can improve the cows body condition score (BCS) from the range 2 - 2,5 to 3 - 3,5; fix the service per conception (S/C) value to Â Â < 2; shortening the calving interval from 18 - 24 months to 13 - 15 months; increase the calf's birth weight to 25 - 28 kg and improve changes in body weight. Keywords : Reproductive, Performance, Cow.